2004
DOI: 10.1038/sj.bjp.0705847
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic mechanisms of benidipine in the ischemic/reperfused heart

Abstract: 1 Considerable evidence indicates that calcium plays a critical role in apoptosis. We have previously shown that benidipine, a vasodilatory calcium channel blocker, attenuates postischemia myocardial apoptosis. The present study was designed to determine the mechanisms by which benidipine exerts its antiapoptotic effect. 2 Adult male rats were subjected to 30 min of ischemia followed by 3 h of reperfusion. Rats were randomized to receive either vehicle or benidipine (10 mg kg À1 , i.v.) 10 min before reperfusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 36 publications
3
29
0
1
Order By: Relevance
“…Our present results clearly demonstrate that SB-203580, a p38 MAPK-specific inhibitor, not only improved cardiac function after reperfusion but, in addition, attenuated I/R-induced myocardial apoptosis and necrosis in hearts, further suggesting the activation of p38 MAPK in myocardial I/R injury. Studies have provided evidence that ischemia alone and I/R activate p38 MAPK in the heart and cultured cardiomyocytes and that administration of SB-203580 reduces myocardial apoptosis, causing recovery after reperfusion (41,42,68). PC treatment, as shown in the present study, significantly attenuated the I/R-induced activation of p38 MAPK and offered cardioprotection against I/R injury, possibly through modulation of p38 MAPK activity.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Our present results clearly demonstrate that SB-203580, a p38 MAPK-specific inhibitor, not only improved cardiac function after reperfusion but, in addition, attenuated I/R-induced myocardial apoptosis and necrosis in hearts, further suggesting the activation of p38 MAPK in myocardial I/R injury. Studies have provided evidence that ischemia alone and I/R activate p38 MAPK in the heart and cultured cardiomyocytes and that administration of SB-203580 reduces myocardial apoptosis, causing recovery after reperfusion (41,42,68). PC treatment, as shown in the present study, significantly attenuated the I/R-induced activation of p38 MAPK and offered cardioprotection against I/R injury, possibly through modulation of p38 MAPK activity.…”
Section: Discussionsupporting
confidence: 49%
“…Recently, several studies demonstrated the involvement of mitogen-activated protein kinases (MAPKs), which play a role in the induction of apoptosis in myocytes exposed to I/R in ischemic injury (43,54,67). Earlier studies demonstrated the activation of ERK1/2 after reperfusion, which is cardioprotective (23,29,41,68). Phosphatidylinositol 3-kinase (PI3K)-Akt signaling is an important mediator of cell survival and promotes survival of cardiomyocytes in vitro and in vivo (2,61,71).…”
mentioning
confidence: 99%
“…Intravenous treatment with benidipine (3 and 10 µg / kg) suppressed not only myocardial necrosis associated with reperfusion after coronary artery ligation but also apoptosis following reperfusion (86,87). These findings suggest that the inhibitory effect on apoptosis contributes to cardiac protection.…”
Section: Cardioprotective Effectsmentioning
confidence: 58%
“…Angiotensin II, an IP 3 -generating agonist, is a potent stimulator of cardiomyocyte hypertrophy that can elevate cytoplasmic Ca 2+ during vasoconstriction, increased blood pressure, and hemodynamic stress. A number of studies have demonstrated that angiotensin II treatment leads to an increase in basal Ca 2+ levels in adult and neonatal cardiomyocytes (Kem et al 1991;Shao et al 1998;Hunton et al 2004), with sustained exposure affecting numerous cellular pathways (Meldrum et al 1996;Liu et al 2004b;Zhang et al 2004) and eventually resulting in cell death (Goldenberg et al 2001;Kajstura et al 1997). Elevating UDP-GlcNAc and O-GlcNAc levels through treatment with glucosamine or the O-GlcNAcase inhibitor PUGNAc attenuates angiotensin IIinduced CCE during I/R injury (Nagy et al 2006).…”
Section: Calcium Homeostasismentioning
confidence: 99%